Chafer Systematic Theology Volume Seven: Doctrinal Summarization - Lewis Sperry Chafer (Dallas Dallas Seminary Press, 1948)
An unabridged original study of Systematic Theology from a Biblical viewpoint
v. 1. Prolegomena. Bibliology. Theology proper.--v.2. Angelology. Anthropology. Hamartiology.--v. 3. Soteriology.--v. 4. Ecclesiology. Eschatology.--v. 5. Christology.--v. 6. Pneumatology.--v. 7. Doctrinal sumarization.--v. 8. Biographical sketch and inde
Keywords: Theology - doctrine